1978
DOI: 10.1007/bf00032383
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the crack tip stress field in DCB adhesive fracture specimens

Abstract: The problem of a cracked adhesive bonded DCB-type fracture specimen has been analyzed using a hybrid stress model finite element analysis which incorporates an advanced crack tip element. Stresses in the near and far fields have been studied as a function of adherend/adhesive modulus ratio and adhesive thickness. The results are compared to monolithic systems with regard to the stress intensity factor and the localization of the singular stress domain associated with the crack tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 8 publications
4
54
0
1
Order By: Relevance
“…Now, there are several reasons why the SERR, G, approach, and not the stress-intensity factor approach, has invariably been used when employing a fracture-mechanics approach to investigate the failure of polymeric-matrix fibre-composite materials and adhesively-bonded joints, see for example [5,7,8,[22][23][24][25][26][27][28]. There is the difficulty of calculating the stressintensity factor around the crack tip in anisotropic and inhomogeneous materials and bonded joints.…”
Section: Introductionmentioning
confidence: 99%
“…Now, there are several reasons why the SERR, G, approach, and not the stress-intensity factor approach, has invariably been used when employing a fracture-mechanics approach to investigate the failure of polymeric-matrix fibre-composite materials and adhesively-bonded joints, see for example [5,7,8,[22][23][24][25][26][27][28]. There is the difficulty of calculating the stressintensity factor around the crack tip in anisotropic and inhomogeneous materials and bonded joints.…”
Section: Introductionmentioning
confidence: 99%
“…The other half of the explanation was offered by Wang (89), who suggested that a second effect was also present. A stress analysis by Wang et al (90) showed that the crack-tip stress field in the adhesive bond differs from that in bulk specimens in that the tensile stresses some distance ahead of the crack tip are higher than expected. As the bond thickness is decreased, this effect becomes more pronounced.…”
Section: Fracture Mechanism: Fracture Behavior In Thin Layersmentioning
confidence: 99%
“…This result raises questions concerning the applicability of linear elastic fracture mechanics to joints of the type tested. It has been previously reported by Wang et al [13] that the region dominated by the elastic crack-tip singularity in an adhesive layer can be quite small, and the characteristic length scale is associated with the adhesive layer thickness, not crack length. Linear elastic results for the joint analyzed here suggest a similar conclusion.…”
Section: Results For a Cracked Elastic-plastic Adhesivementioning
confidence: 99%